(untitled) (World Bulletin of Public Health, 2023)
The article presents the results of clinical studies on the possibility of using laser and photodynamic therapy in the treatment of purulent-necrotic processes of the lower extremities in patients with diabetes mellitus. To this end, the authors conducted clinical studies of 110 patients operated in the department of purulent-septic surgery of the ASMI clinic. Studies have shown that after the opening of the purulent-necrotic process of the lower extremities in patients with diabetes mellitus with the use of laser therapy in combination with photosensitization, accelerated regression of inflammatory infiltration, complete cessation of purulent-necrotic discharge, wound cleansing and activation of regeneration processes